Post-Induction High Adalimumab Drug Levels Predict Biological Remission at Week 24 in Patients With Crohn's Disease. Issue 10 (6th October 2021) - Zittan, Eran; Steinhart, A. Hillary; Goldstein, Pavel; Milgrom, Raquel; Gralnek, Ian M.; Silverberg, Mark S.
Abstract : INTRODUCTION: We investigated whether early adalimumab drug levels (ADL) at week 4 predicted biological remission at week 24. METHODS: In a prospective study, we assessed clinical and biological remission at weeks 0, 4, 12, and 24 after induction of adalimumab in 33 patients with Crohn's disease. Disease activity was determined by the Harvey-Bradshaw Index, ileocolonoscopy reports, cross-sectional imaging, C-reactive protein (CRP), and fecal calprotectin (FC) levels. Clinical remission was defined as Harvey-Bradshaw Index <5. Biological remission was defined as a combination of FC < 200 μg/g and CRP <5 μg/mL. ADL trough levels were tested using a liquid phase, mobility shift assay. RESULTS: At 24 weeks, 18/33 (55%) of the patients were with biological remission. Ten (30%) patients required dose escalation or withdrawal from adalimumab by week 24 because of lack of response and exhibited significantly higher FC ( P = 0.003) and CRP ( P = 0.002). ADL levels at week 4 (19.8 μg/mL vs 10.2 μg/mL, P = 0.001) were significantly higher in patients with biological remission vs nonresponders at week 24. ADL levels at week 4 were a good predictor of biological remission at week 24, with area under the curve 0.86, 95% confidence interval (1.1; 1.67) and for combined biological and clinical remission, with area under the curve 0.8. The best ADL cutoff at week 4 that predicted biological remission at week 24 was 13.9 μg/mL (sensitivity 94.4% and specificity 73.3%). DISCUSSION: In individuals with Crohn's disease, higher adalimumab drug levels at week 4 (>13.9 μg/mL) were significantly associated with biological remission at week 24.